Anti-epileptic potentials of the partitioned fractions of chamaecrista mimosoides - N. Medugu, Asinamai; Yakubu, James; I. Marte, Hussaini; ., Timothy; Yerima, S. (International Journal of Pharmacology and Toxicology, 2020)
This research work aimed to establish scientific basis for the use of Chamaecrista mimosoides, in traditional medicine as anti-epileptic medication. The whole plant part of Chamaecrista mimosoides was extracted with ethanol and screened for phytochemicals. Acute toxicity study was carried out using Lorkeâ€™s method and the antiepileptic activity was evaluated using maximal electroshock induced seizure test in day-old chicks, pentylenetetrazole (PTZ) and strychnine using mice. The phytochemical study revealed the presence of saponins, cardiac glycosides, tannins, flavonoids, terpenoids and cardenolides. Both the chloroform, ethylacetate and n-butanol portions at 100, 250, and 500mg/kg body weight did not protect the chicks against tonic hind limb extension (THLE) in maximal electro-shock test (MEST). The chloroform and n-butanol portions at doses of 250 and 500 mg/kg body weight protected 40% and 60% of mice against clonic spasm induced by pentylenetetrazole, while ethyl-acetate soluble portion did not protect the mice against clonic spasm induced by pentylenetetrazole at all doses used when compared to Valproic acid (200 mg/kg) protected all the mice (100%) against clonic spasm induced by pentylenetetrazole. The chloroform soluble portion at the doses of 100, 250 and 500 mg/kg body weight protected 40%, 100%, 100% against death induced by strychnine, while ethylacetate and n-butanol portions did not protect the rats against death induced by strychnine but prolonged the onset of convulsion. In all the tests, phenobarbitone (20 mg/kg) was used as positive control and protected 80% of mice against convulsion induced by strychnine. The antiepileptic investigation suggests that the chloroform portion of Chamaecrista mimosoides has a promising antiepileptic activity.Â Â